Evaluating seismic stability of reinforced soil slopes using the limit equilibrium method: influence of geosynthetic strength indicators - Chen, Xin; Zhou, Zheng; Zhu, Yuming; Pu, Shikun; Zhang, Dengke; Li, Erbing (Frontiers in Physics, 2025)
Seismic stability of soil slopes is a critical issue within engineering geology, with a particular emphasis on understanding how geosynthetic strength indicators influence the stability of reinforced slopes. This paper employs the limit equilibrium method, in conjunction with the log spiral curve model, to evaluate the seismic stability of reinforced soil slopes considering varying pullout strength indicators. The proposed method is verified by comparing with a same case in the corresponding reference. Then, effects of the non-uniform pullout strength distribution on the seismic reinforcement of slopes is revealed theoretically by changing parameters such as slope angles, friction angles of fill soils, and design length of geosynthetics. The results indicated that when lengths of the geosynthetics are reduced, the seismic yield accelerations calculated using the ultimate bearing capacity is significantly smaller than that obtained using the ultimate pullout strength. It is suggested that the nonuniform pullout strength distribution should be taken into consideration to ensure the stability of slopes under seismic actions. Additionally, this study provides new perspectives and methods for the theoretical study and engineering application of geosynthetic reinforcement techniques.